Strategic Innovation: A Systematic Review of Literature. - Ferney Virgüez, Jonathan; Castro-Silva, Hugo Fernando; Chaparro-Pérez, Cindy Johana; Angarita-López, Jhonn Jairo (AiBi Journal of Research, Administration and Engineering, 2020)
This article aims to identify the conceptualization of strategic innovation and its importance for competitiveness. A systematicliterature review was carried out using Tranfield (2003) methodology and an analysis of trends on the subject using the software tool to buildand visualize VOSviewer® bibliometric networks. The results obtained reflect that the study of the subject is relatively new for the academiccommunity and that it has progressed substantially in recent years, however, it is still a field where the general panorama is just beginning totake shape. Finally, it became clear that strategic innovation is a key factor for generating a value offer for stakeholders and an important toolto maintain and promote competitiveness and the development of sustainable competitive advantages.
Keywords: Innovation, Strategic Innovation, Competitiveness, Literature Review, Tranfield.